Дизайн інтер’єру кав’ярні-кондитерської для людей з особливими потребами у м. Львові на вул. Газовій, 7 - Солук, Наталія Василівна; Soluk, Nataliia Vasylivna (Національний університет "Львівська політехніка", 2024)
Актуальність теми полягає у необхідності створення інклюзивних громадських просторів, що враховують потреби людей з інвалідністю та сприяють їхній соціалізації. Об’єкт проєктування: розробка інтер’єрного простору приміщення кав’ярні-кондитерської площею 136,19 м2 за адресою вул. Газова, 7. Предмет проєктування: дизайн інтер’єру інклюзивної кав’ярні з урахуванням принципів універсального дизайну. Мета роботи: створити доступний, комфортний і естетичний простір, що відповідає потребам різних груп користувачів і сприяє працевлаштуванню людей із синдромом Дауна. У першому розділі розглянуто концепцію інклюзивного середовища, простежено етапи становлення інклюзивного дизайну в архітектурі та інтер’єрі, а також проаналізовано чинні нормативні документи. Виокремлено основні принципи універсального дизайну, що забезпечують зручність, безпеку та доступність для усіх. Другий розділ присвячено аналізу закордонного та українського досвіду у сфері інклюзивного дизайну кав’ярень. Досліджено приклади закладів, адаптованих до потреб осіб із порушеннями слуху, зору, опорно-рухового апарату. Особливу увагу приділено технічним та композиційним рішенням, що впливають на зручність і доступність простору, а також виявлено типові бар’єри, які перешкоджають реалізації інклюзивного середовища. У третьому розділі представлено авторське проєктне рішення: сформовано функціонально-планувальну структуру інтер’єру, обрано стилістичне спрямування. Проаналізовано вплив кольору, освітлення, текстур і матеріалів на 7 психологічний стан користувачів. Запропоновано комплекс ергономічних і сенсорних рішень, які формують дружнє, адаптивне середовище. У четвертому розділі проаналізовано основні витрати на реалізацію проєкту, враховано матеріали, меблі та обладнання відповідно до обраної концепції.

The relevance of the topic lies in the need to create inclusive public spaces that consider the needs of people with disabilities and promote their socialization. Object of design: development of the interior space of a cafe-confectionery with an area of 136.19 m2 at 7 Gazova Street. Subject of design: interior design of an inclusive cafe based on the principles of universal design. The purpose of the work is to create an accessible, comfortable and aesthetically appealing space that meets the needs of different user groups and promotes the employment of people with Down syndrome. The first chapter examines the concept of inclusive environment and its significance in contemporary society, traces the history of inclusive design in architecture and interiors. It analyzes the current building codes and identifies the principles of universal design as the foundation for creating a safe and user-friendly environment for people with different physical, sensory, and cognitive needs. The second chapter is dedicated to the analysis of Ukrainian and foreign examples of inclusive cafes. It considers different approaches to inclusion — from involving people with disabilities in the workplace to designing interiors adapted for people with visual or hearing impairments. Special attention is paid to technical, compositional, and functional solutions that affect accessibility and convenience. In addition, the challenges of implementing inclusive design in public facilities are discussed, and typical environmental barriers are outlined. The third chapter presents the author’s design project of an inclusive cafe- confectionery. It covers the design brief and initial data, based on which the functional and spatial structure of the interior is developed. A stylistic solution is proposed, 9 considering the needs of the target audience and the overall concept of inclusiveness. The influence of key design tools — lighting, color, textures, and materials — on the psychological perception and user comfort is analyzed. Particular attention is paid to ergonomic, sensory, and accessible solutions that form a barrier-free environment for people with different needs. The fourth chapter discusses the economic part of the project. The expenses for the project implementation and the author’s object are analyzed.
Interior design of a coffee and pastry shop for people with special needs in Lviv at 7 Gazova Street
Keywords: 6.022.03.03; інклюзивний дизайн; кав’ярня-кондитерська; універсальний простір; люди з інвалідністю; синдром Дауна; дизайн середовища; inclusive design; cafe-confectionery; universal space; people with disabilities; Down syndrome; environmental design